Pengaruh Bauran Pemasaran Jasa Terhadap Pengambilan Keputusan Mahasiswa Baru Dalam Memilih Program Studi S1 Manajemen Fakultas Ekonomi Dan Bisnis Universitas Trunojoyo Madura - Febrianto, Vicky Tri; Purnomo, Hadi (Eco-Entrepreneur, 2023)
This study aims to determine the effect of the service marketing mix on the decision making of new students in choosing the Bachelor of Management study program, Faculty of Economics and Business, University of Trunojoyo, Madura. The object of this research is new students (Class of 2022). The method used is a quantitative method with data collection techniques through questionnaires.The results of this study indicate that the service marketing mix which consists of product, price, place, promotion, people, physical evidence, and process variables has a positive and significant influence on the decision making of new students in choosing the S1 Management study program, Faculty of Economics and Business, University of Trunojoyo Madura. As well as the promotion variable has a dominant influence on the decision making of new students in choosing the Bachelor of Management study program, Faculty of Economics and Business, University of Trunojoyo Madura.